2016
DOI: 10.12816/0033277
|View full text |Cite
|
Sign up to set email alerts
|

Stress Management and Its Contributing Factors among Post-Graduate Students : A Comparative Analysis

Abstract: Stress has become an important topic in academic circle. Many scholars in the field of behavioural science have carried out extensive research on stress and its outcomes and concluded that the topic needed more attention. This study checked the prevalence of stress in college students and its association with three factors. It explored the components of academic stress among post graduate students and their effects on overall academic life, intrapersonal life and social life. A questionnaire based study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Overall resident students (M = 60.3, SD = 23.0) were more stressed than non-resident students (M = 59.7, SD = 21.7). This finding is consistent with studies conducted by various researches at specific universities on stressors encountered by university students (Kabir et al, 2018;Parveen, 2016).…”
Section: Stressors Among Teacher Education Studentssupporting
confidence: 93%
See 2 more Smart Citations
“…Overall resident students (M = 60.3, SD = 23.0) were more stressed than non-resident students (M = 59.7, SD = 21.7). This finding is consistent with studies conducted by various researches at specific universities on stressors encountered by university students (Kabir et al, 2018;Parveen, 2016).…”
Section: Stressors Among Teacher Education Studentssupporting
confidence: 93%
“…A study was conducted between Commerce and Law students in Aligarh Muslim University, Aligarh (UP), India. This research found the pervasiveness of stress in college students and its relationship with academic life, intrapersonal life and social life (Parveen, 2016). The findings indicated that resident students experienced more stressors than non-resident students.…”
Section: Empirical Literature Reviewmentioning
confidence: 79%
See 1 more Smart Citation